Microcosmus anchylodeirus (Ascidiacea, Pyuridae) introduced in the Mediterranean Sea - Monniot, Françoise (Zootaxa, 2016)
Several specimens of Microcosmus anchylodeirus Traustedt, 1883 were successively collected by dives along the shore of southern Corsica. With a corrugated tunic covered with all kinds of epibionts they are difficult to notice on the rocks and are recorded for the first time from Mediterranean Sea. These ascidians correspond well internally and externally to Atlantic specimens from the Caribbean islands and also to those described from Brazil. Pacific specimens identified as Microcosmus multitentaculatus Tokioka, 1953 from Japan and Korea have been examined and are now considered as junior synonyms of Microcosmus anchylodeirus, a species whose origin is not known.